Pengaruh Return On Assets (Roa) Dan Debt To Equity Ratio (Der) Terhadap Harga Saham PT Gudang Garam Tbk (Ggrm) Periode 2014-2023 - Eka Yuliarti, Shabilla; Mardiati, Dijan (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
Abstrak. This study aims to determine the effect of Return on Assets (ROA) and Debt to Equity Ratio (DER) both partially and simultaneously on the share price of PT Gudang Garam Tbk during the period 2014-2023. The research method used is a quantitative approach that is associative in nature, with simple and multiple linear regression analysis techniques. The population of this study is the financial statements of PT Gudang Garam Tbk and the samples taken are the financial position report, income statement, and stock price overview for the last 10 years from 2014-2023. The results showed that Return on Assets (ROA) had a significant effect on stock prices, with a significance value of 0.006 <0.05 and tcount 3.737> ttable 2.3646. Debt to Equity Ratio (DER) has no significant effect on stock prices, with a significance value of 0.340> 0.05 and tcount 1.014 < t table 2.3646. Return On Assets (ROA) and Debt to Equity Ratio (DER) simultaneously have a significant effect on stock prices, with a significance value of 0.016 <0.05 and an Fcount value of 7.884> Ftable 4.74. Keywords: Return On Assets (ROA); Debt to Equity Ratio (DER); Share Price